Mortality pattern in a tertiary care teaching hospital in North Karnataka, India - Shankar, Gowri; Kalburgi, Eshwar B. (International Journal Of Community Medicine And Public Health, 2019)
Background: India is undergoing rapid epidemiological transition due to economic and social change. The pattern of mortality is a key indicator of the long term health effects. Mortality data indicates the health of the population under study. Hence this study was done to know the socio demographic profile and mortality pattern of all deaths in a tertiary care teaching hospital in North Karnataka, India. Methods: A one year retrospective study of all deaths in Hangal Sri Kumareshwar Hospital and Research Center, Navanagar, Bagalkot, Karnataka State, India was done of the year 2017, after ethical clearance and Institutional Review Board. The case records of all deaths from Medical Record Department were analyzed for socio demographic profile and mortality pattern. The deaths had been classified according to International Classification of Diseases-10th revision. Data was analyzed using percentages and chi-square test. Results: Out of 357 deaths in the year 2017, 214 (59.94%) were males and 143 (40.06%) were females. Maximum deaths were between 15 to 60 years of age contributing to 43.14% of the total followed by deaths in more than 60 years of age (35.29%). Non-communicable diseases contributed to 70.03% of the total deaths. Conclusions: Non communicable diseases are on the rise in the urban and rural communities of the study area. Preventive care is the need of the hour and it can be achieved through health education and screening of the high risk population.